Techno-economic Analysis in the Modification of 100 TEUs Container Carrier by Using LNG as Dual Fuel System - Santoso, Agoes; Cahyono, Beny; Jadmiko, Edi; Garsia, Kevin (International Journal of Marine Engineering Innovation and Research, 2025)
Indonesia is no longer known as an oil exporter country but Indonesia has a large deposit of natural gas. This situation will bring the conversion from using fuel oil to gas. It will also support IMO Regulation such as MARPOL 73/78 Annex VI Tier III which was stringent in the regulation to bring the world to achieve near zero emission level. One of the methods to comply with IMO tier III is using gas as a fuel. Therefore, the ship efficiency can be overcome by two aspects simultaneously, cheaper and cleaner gas as marine engine fuel. In this paper, LNG as fuel will be applied to 100 TEUs Container Carrier which is consider several technical aspects when the existing ship is modified so that natural gas can be used safely and well. Things to consider in this LNG re-design are; the volume of tank, bunkering station system, and the Gas Valve Unit (GVU). In addition, this design will also analyze the costs required to modify the vessel so that it can use dual fuel (MDO and LNG) as well as cost comparison when using single fuel (MDO).